Pandangan Ulama Pesantren Di Kabupaten Garut Tentang Istri Bekerja Di Luar Rumah - Abdillah, Syaik; Nurmala, Rika (STAI Al Musaddadiyah Garut, 2023)
Women who have husbands and work outside the home are a common phenomenon in Indonesia, including in the Garut region. Wives work outside the home, either during the day or at night, this is a common fact and phenomenon in Garut. Of course, not a few of these phenomena get comments from the community, because it involves women's activities which are considered vulnerable to temptation and interference. This research departs from the desire to answer how the legal status of women or wives who work outside the home to help their husbands earn family income, in this case involving scholars who contribute to the internalization of religious moral values followed by the Garut community. What is the view of Garut Islamic boarding school scholars on the legal status of wives who work outside the home in Garut. This research uses historical, and sociological approaches. The historical approach used to read a person's opinion about the message of scripture cannot be separated from the historical context in which he or she interprets it. While a sociological approach is used to identify, explain the ideas of pesantren scholars in the context of the particular social situation in which they live. The results of the study stated that wives working outside the home, according to Islamic boarding school scholars in Garut is not prohibited by religion, as long as it is in the framework of building the benefits of married life and obtaining permission from the husband. Keywords: Islamic law, Ulama, pesantren, working wife;